Preparation method and application of silicon-carbon composite material

By using the PECVD method to grow carbon layers at low temperature on the surface of silicon carbon particles, the problem of insufficient conductivity and cyclic performance of silicon carbon anode materials under high magnification conditions is solved, and high-efficiency and low-energy consumption silicon carbon composite materials are achieved, which improves the material magnification and cycling performance.

CN119170784AInactive Publication Date: 2024-12-20ZHEJIANG JIAXING XINGHAN NANO TECH CO LTD

Patent Information

Application Number
CN202411634387.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing silicon-carbon anode materials have insufficient conductivity and cycling performance under high magnification conditions. The traditional CVD method requires high temperatures to lead to high energy consumption and low efficiency, and has adverse effects on amorphous nano-silicon particles.

Method used

The carbon layer is grown at a low temperature on the surface of silicon carbon particles by a controllable PECVD method, and chemical vapor deposition is enhanced through plasma to improve the conductivity and integrity of the carbon layer, and enhance the magnification and cyclic performance of the material.

Benefits of technology

It realizes the preparation of high conductivity and uniformity carbon layers at low temperatures, improves the rate performance and cycle stability of the material, reduces the preparation temperature and energy consumption, and is suitable for low-cost large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170784A_ABST
    Figure CN119170784A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a silicon-carbon composite material. The preparation method comprises the following steps: under a protective atmosphere, introducing a carbon source gas, and carrying out plasma enhanced chemical vapor deposition on silicon-carbon matrix raw material particles to obtain the silicon-carbon composite material coated with a carbon layer on the surface. Through the PECVD method, the carbon layer is grown on the surface of the silicon carbon particle at low temperature, the deposition process can be rapidly controlled and adjusted by controlling the power of the plasma power supply so as to obtain a high-conductivity completely-coated carbon layer structure, the temperature required in the process is low, the efficiency is high, and the deposition speed can be increased by more than 5 times; meanwhile, the utilization rate of carbon source gas is high, energy consumption is low, and the method is more suitable for low-cost large-scale preparation. According to the controllable PECVD method for growing the carbon layer on the surface of the silicon-carbon negative electrode, the orderliness and integrity of the surface carbon layer can be effectively improved, so that the material has better cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of silicon-carbon composite materials, and relates to a method for preparing a silicon-carbon composite material and applications thereof, and in particular to a method for preparing a high-rate and long-cycle silicon-carbon negative electrode material for a lithium-ion battery and applications thereof. Background Art

[0002] At present, in the conventional technical scheme of silicon-carbon negative electrode materials, in order to improve the conductivity and cycle performance of the material, a carbon layer is generally coated on the surface of the negative electrode particles. The coating methods include solid phase coating, liquid phase coating and gas phase coating or a combination of several methods, but the control of the structure of the coating layer is not very precise, and the conductivity and integrity of the coating layer itself are still relatively limited.

[0003] At present, it is usually based on the traditional CVD method to construct a two-dimensional surface carbon layer on the surface of silicon-carbon particles. However, if the traditional CVD method is used to construct a relatively complete carbon layer, the deposition process generally requires a very high temperature (about 800~1000℃), high energy consumption, low efficiency, and for silicon-carbon particles with amorphous nano-silicon, the higher temperature may cause the nano-silicon to crystallize, which has an adverse effect on its lithium storage capacity. If a lower temperature (500~600℃) is used to prepare the carbon layer, the quality of the generated carbon layer is poor and the conductivity is poor, which makes the material perform poorly under high rate conditions. Moreover, the uniformity of the coating layer is not good at low temperatures, which causes the electrolyte to contact the silicon element, thereby adversely affecting the cycle performance.

[0004] Therefore, how to find a more appropriate way to solve the above-mentioned problems existing in the existing technical solutions has become one of the urgent problems to be solved by many front-line researchers and scientific research enterprises. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a method for preparing a silicon-carbon composite material and its application, in particular, a method for preparing a high-rate and long-cycle silicon-carbon negative electrode material for lithium-ion batteries. The present invention uses a controllable PECVD method to grow a carbon layer on the surface of silicon-carbon negative electrode particles, so that ions and electrons have more transmission channels and faster transmission speeds, so that the material has better rate performance, and at the same time, the orderliness and integrity of the carbon layer are improved, so that the material has better cycle stability.

[0006] The present invention provides a method for preparing a silicon-carbon composite material, comprising the following steps: In a protective atmosphere, carbon source gas is introduced, and plasma enhanced chemical vapor deposition is performed on silicon-carbon matrix raw material particles to obtain a silicon-carbon composite material with a carbon layer coated on the surface.

[0007] Preferably, the plasma enhanced chemical vapor deposition is specifically low temperature plasma enhanced chemical vapor deposition; The gas temperature of the plasma enhanced chemical vapor deposition is 20-500°C.

[0008] Preferably, the silicon-carbon matrix raw material particles include one or more of silicon-carbon particles doped with silicon and carbon, silicon-carbon particles with silicon compounded inside and / or on the surface of porous carbon particles, silicon-carbon particles with carbon compounded inside and / or on the surface of porous silicon particles, and silicon oxide / carbon particles. The particle size of the silicon-carbon matrix raw material particles is 0.1-15 μm.

[0009] Preferably, the mass content of silicon in the silicon-carbon matrix raw material particles is 0.1% to 60%; The silicon-carbon matrix raw material particles include heated silicon-carbon matrix raw material particles.

[0010] Preferably, the heating temperature is 1-500°C; The heating rate is 1-20°C / min.

[0011] Preferably, the introducing of the carbon source gas is specifically to introduce the carbon source gas under the condition of using the protective gas as the carrier gas; The carbon source gas includes one or more of methane, acetylene, ethylene, propylene and propane; The protective gas includes one or more of an inert gas, nitrogen, and an inert gas / hydrogen mixed gas.

[0012] Preferably, the flow rate of the protective gas is 0.1-100 L / min; The flow rate of the carbon source gas is 0.1-20 L / min.

[0013] Preferably, the power of the plasma enhanced chemical vapor deposition is 0.1~1KW; The plasma enhanced chemical vapor deposition time is 5 to 200 minutes.

[0014] Preferably, the silicon-carbon composite material comprises a silicon-carbon negative electrode material; The silicon-carbon composite material is specifically a silicon-carbon negative electrode material for lithium-ion batteries.

[0015] The present invention also provides the use of the silicon-carbon composite material prepared by the preparation method described in any one of the above technical solutions in the negative electrode material of a secondary battery.

[0016] The present invention provides a method for preparing a silicon-carbon composite material, comprising the following steps: in a protective atmosphere, a carbon source gas is introduced, and plasma enhanced chemical vapor deposition is performed on silicon-carbon matrix raw material particles to obtain a silicon-carbon composite material with a surface coated with a carbon layer. Compared with the prior art, the present invention grows a carbon layer on the surface of silicon-carbon particles at low temperature by a PECVD method, which can not only quickly control and adjust the deposition process by controlling the power of the plasma power supply, thereby obtaining a highly conductive and fully coated carbon layer structure, but also requires a low temperature and high efficiency in the process, and the deposition rate can be increased by more than 5 times, and the utilization rate of the carbon source gas is high, which is more suitable for low-cost large-scale preparation. The controllable PECVD method provided by the present invention for growing a carbon layer on the surface of silicon-carbon negative electrode particles has a more uniform and controllable carbon layer structure, so that ions and electrons have more transmission channels and faster transmission speeds, so that the material has better rate performance and cycle performance.

[0017] The present invention grows a carbon layer on the surface of silicon-carbon particles by a PECVD method instead of using an ordinary CVD method to grow a carbon layer, and can prepare a carbon layer with high conductivity and uniformity at a relatively low temperature, generally at 20-500°C. Moreover, the plasma power source used in the present PECVD method can be a radio frequency power source, a microwave power source, or other plasma power sources such as a DC power source; the silicon-carbon particles used can be various forms of silicon-carbon particles or silicon-carbon precursor particles, including but not limited to silicon-carbon particles obtained by vapor deposition of silicon on porous carbon particles, or silicon-carbon particles obtained by a sand milling composite method, or particles prepared by a silicon oxide precursor obtained by sublimation and condensation of silicon powder and silicon dioxide powder, or silicon-carbon particles obtained by vapor deposition of carbon on porous silicon particles, or particles coated with one or more carbon layers or other material layers on the surface of the above particles, all of which are suitable for the present method. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a SEM scanning electron microscope image of silicon carbon particles after carbon layer deposition by PECVD method in an embodiment of the present invention; Figure 2 This is the XRD diffraction pattern of the silicon-carbon composite material prepared in the embodiment of the present invention. DETAILED DESCRIPTION

[0019] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0020] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0021] There is no particular restriction on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure raw materials or raw materials of conventional purity used in the field of lithium ion silicon-carbon negative electrode preparation.

[0022] The present invention provides a method for preparing a silicon-carbon composite material, comprising the following steps: In a protective atmosphere, carbon source gas is introduced, and plasma enhanced chemical vapor deposition is performed on silicon-carbon matrix raw material particles to obtain a silicon-carbon composite material with a carbon layer coated on the surface.

[0023] In the present invention, the plasma enhanced chemical vapor deposition is preferably low temperature plasma enhanced chemical vapor deposition.

[0024] In the present invention, the gas temperature of the plasma enhanced chemical vapor deposition is preferably 20-500°C, more preferably 50-450°C, more preferably 100-400°C, more preferably 150-350°C, more preferably 200-300°C. Specifically, it can be 200-500°C, or 350-450°C.

[0025] In the present invention, the silicon-carbon matrix raw material particles preferably include one or more of silicon-carbon particles doped with silicon and carbon, silicon-carbon particles with silicon compounded inside and / or on the surface of porous carbon particles, silicon-carbon particles with carbon compounded inside and / or on the surface of porous silicon particles, and silicon oxidized carbon particles, and more preferably silicon-carbon particles doped with silicon and carbon, silicon-carbon particles with silicon compounded inside and / or on the surface of porous carbon particles, silicon-carbon particles with carbon compounded inside and / or on the surface of porous silicon particles, or silicon oxidized carbon particles.

[0026] In the present invention, the D50 particle size of the silicon-carbon matrix raw material particles is preferably 0.1-15 μm, more preferably 1-11 μm, and more preferably 5-7 μm.

[0027] In the present invention, the mass content of silicon in the silicon-carbon matrix raw material particles is preferably 0.1% to 60%, more preferably 10% to 50%, and more preferably 20% to 40%.

[0028] In the present invention, the silicon-carbon matrix raw material particles may be heated or not heated before plasma enhanced chemical vapor deposition. Specifically, the silicon-carbon matrix raw material particles preferably include heated silicon-carbon matrix raw material particles.

[0029] In the present invention, the heating temperature is preferably 1-500°C, more preferably 10-450°C, more preferably 50-400°C, more preferably 100-350°C, more preferably 150-300°C.

[0030] In the present invention, the heating rate is preferably 1-20°C / min, more preferably 5-15°C / min, more preferably 5-10°C / min, and specifically 5°C / min.

[0031] In the present invention, the carbon source gas is preferably introduced under the condition that a protective gas is used as a carrier gas.

[0032] In the present invention, the carbon source gas preferably includes one or more of methane, acetylene, ethylene, propylene and propane, and more preferably methane, acetylene, ethylene, propylene or propane.

[0033] In the present invention, the protective gas preferably includes one or more of an inert gas, nitrogen, and an inert gas / hydrogen mixture, and more preferably an inert gas, nitrogen, or an inert gas / hydrogen mixture.

[0034] In the present invention, the flow rate of the protective gas is preferably 0.1 to 100 L / min, more preferably 10 to 80 L / min, and more preferably 30 to 60 L / min.

[0035] In the present invention, the flow rate of the carbon source gas is preferably 0.1 to 20 L / min, more preferably 1 to 15 L / min, and more preferably 6 to 10 L / min.

[0036] In the present invention, the power of the plasma enhanced chemical vapor deposition is preferably 0.1-1 KW, more preferably 200-800 W, and more preferably 400-600 W.

[0037] In the present invention, the time of the plasma enhanced chemical vapor deposition is preferably 5 to 200 min, more preferably 10 to 180 min, more preferably 30 to 150 min, more preferably 60 to 120 min, more preferably 80 to 100 min.

[0038] In the present invention, the silicon-carbon composite material preferably includes a silicon-carbon negative electrode material.

[0039] In the present invention, the silicon-carbon composite material is preferably a silicon-carbon negative electrode material for a lithium-ion battery.

[0040] The present invention provides the use of a silicon-carbon composite material prepared by the preparation method described in any one of the above technical solutions in a negative electrode material for a secondary battery.

[0041] The present invention is to complete and refine the overall technical solution, better ensure the structure of the silicon-carbon composite material, and further improve the electrical properties of the silicon-carbon composite material. The preparation method of the high-rate and long-cycle silicon-carbon negative electrode material for lithium-ion batteries may specifically include the following contents: 1. Raw materials: The matrix raw material particles can be various forms of silicon-carbon particles or silicon-carbon precursor particles, including but not limited to silicon-carbon particles obtained by vapor deposition of silicon on porous carbon particles, or silicon-carbon particles obtained by a sand grinding composite method, or particles prepared from a silicon oxide precursor obtained by sublimation and condensation of silicon powder and silicon dioxide powder, or silicon-carbon particles obtained by vapor deposition of carbon on porous silicon particles, or particles having one or more carbon layers or other material layers coated on the surface of the above particles.

[0042] 2. Heating: Place the matrix raw material particles in a tubular furnace, first vacuum the cavity, and then heat to 1~300℃ under the protection of inert gas such as nitrogen or argon, with a heating rate of 5℃ / min.

[0043] 3. Plasma enhanced vapor deposition: When an inert gas is used as a carrier gas, a carbon source gas (such as methane, acetylene, propylene, propane, etc.) is passed through, and the gas molecules in the cavity are inductively excited by an external plasma power supply to make the gas molecules reach a plasma state. Carbon atoms are rapidly deposited on the surface of the matrix raw material particles, and the gas flow rate and power supply parameters are adjusted at the same time to obtain a carbon layer with controllable thickness and uniformity.

[0044] 4. Cooling: After the PECVD process is completed, stop the plasma power supply, turn off the carbon source gas, and maintain the inert gas flow. The temperature of the deposited particles drops to room temperature before discharging.

[0045] The above content of the present invention provides a preparation method and application of high-rate and long-cycle silicon-carbon negative electrode materials for lithium-ion batteries. The present invention grows a carbon layer on the surface of silicon-carbon particles at low temperature through the PECVD method. Not only can the deposition process be quickly controlled and adjusted by controlling the power of the plasma power supply to obtain a highly conductive and fully coated carbon layer structure, but also the temperature required in the process is low and the efficiency is high. The deposition rate can be increased by more than 5 times, which is more suitable for low-cost large-scale preparation. The controllable PECVD method provided by the present invention for growing a carbon layer on the surface of silicon-carbon negative electrode particles enables ions and electrons to have more transmission channels and faster transmission speeds, so that the material has better rate performance and cycle performance when used.

[0046] The present invention grows a carbon layer on the surface of silicon-carbon particles by a PECVD method instead of using an ordinary CVD method to grow a carbon layer, and can prepare a carbon layer with high conductivity at a relatively low temperature, generally at 20-500°C. Moreover, the plasma power source used in the present PECVD method can be a radio frequency power source, a microwave power source, or other plasma power sources such as a DC power source; the silicon-carbon particles used can be various forms of silicon-carbon particles or silicon-carbon precursor particles, including but not limited to silicon-carbon particles obtained by vapor deposition of silicon on porous carbon particles, or silicon-carbon particles obtained by a sand milling composite method, or particles prepared by a silicon oxide precursor obtained by sublimation and condensation of silicon powder and silicon dioxide powder, or silicon-carbon particles obtained by vapor deposition of carbon on porous silicon particles, or particles coated with one or more carbon layers or other material layers on the surface of the above particles, all of which are suitable for the present method.

[0047] In order to further illustrate the present invention, a preparation method of a silicon-carbon composite material provided by the present invention and its application are described in detail below in combination with examples. However, it should be understood that these examples are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following examples. Example 1

[0048] The porous silicon-carbon precursor powder is loaded into the PECVD chamber, and the powder is made more uniform during the deposition process by flipping the chamber and stirring the inside. The powder temperature is 25°C.

[0049] Next, turn on the vacuum pump of the chamber and evacuate the chamber to 10Pa.

[0050] Then, acetylene gas was introduced and gas replacement was performed twice at a flow rate of 100 ml / min.

[0051] Afterwards, the acetylene flow rate was adjusted to 50 ml / min, the argon flow rate was adjusted to 10 ml / min, and the vacuum degree was controlled within 50 Pa. The plasma emission power supply was turned on, the power supply power was set to 200 W, and plasma was excited to perform gas phase chemical deposition. The duration was 20 minutes, and the preparation of CVD silicon-carbon material was completed to obtain sample No. 1. Example 2

[0052] The porous silicon-carbon precursor powder is loaded into the PECVD chamber. The powder is made more uniform during the deposition process by flipping the chamber and stirring the chamber internally. The powder temperature is heated from 25°C to 100°C at a heating rate of 5°C / min.

[0053] Next, turn on the vacuum pump of the chamber and evacuate the chamber to 10Pa.

[0054] Then, acetylene gas was introduced and gas replacement was performed twice at a flow rate of 100 ml / min.

[0055] Afterwards, the acetylene flow rate was adjusted to 100 ml / min, the argon flow rate was adjusted to 10 ml / min, and the vacuum degree was controlled within 50 Pa. The plasma emission power supply was turned on, the power supply power was set to 200 W, and plasma was excited to perform gas phase chemical deposition. The duration was 10 minutes, and the preparation of CVD silicon-carbon material was completed to obtain sample No. 2. Example 3

[0056] The porous silicon-carbon precursor powder is loaded into the PECVD chamber. The powder is made more uniform during the deposition process by flipping the chamber and stirring the chamber internally. The powder temperature is heated from 25°C to 200°C at a heating rate of 5°C / min.

[0057] Next, turn on the vacuum pump of the chamber and evacuate the chamber to 10Pa.

[0058] Then, acetylene gas was introduced and gas replacement was performed twice at a flow rate of 100 ml / min.

[0059] Afterwards, the acetylene flow rate was adjusted to 100 ml / min, the argon flow rate was adjusted to 10 ml / min, and the vacuum degree was controlled within 50 Pa. The plasma emission power supply was turned on, the power supply power was set to 200 W, and plasma was excited to perform gas phase chemical deposition. The duration was 20 minutes, and the preparation of CVD silicon-carbon material was completed to obtain sample No. 3. Comparative Example 1

[0060] The porous silicon-carbon precursor powder is loaded into the CVD chamber, and the powder is made more uniform during the deposition process by flipping the chamber and stirring the chamber internally. The powder temperature is heated from 25°C to 600°C at a heating rate of 5°C / min.

[0061] Next, turn on the vacuum pump of the chamber and evacuate the chamber to 10Pa.

[0062] Then, acetylene gas was introduced to perform atmospheric pressure gas replacement at a flow rate of 100 ml / min for 30 min.

[0063] Afterwards, the acetylene flow rate was adjusted to 100 ml / min and the argon flow rate was adjusted to 50 ml / min to perform vapor phase chemical deposition for 60 minutes to complete the preparation of CVD silicon-carbon material and obtain sample No. 4.

[0064] The materials prepared in the examples of the present invention and the comparative examples were characterized.

[0065] See also Figure 1 , Figure 1 This is a SEM scanning electron microscope image of silicon carbon particles after carbon layer deposition by PECVD method according to an embodiment of the present invention.

[0066] See also Figure 2 , Figure 2 This is the XRD diffraction pattern of the silicon-carbon composite material prepared in the embodiment of the present invention.

[0067] The materials prepared in the examples of the present invention and the comparative examples were tested.

[0068] 50g of each sample 1, 2, 3, and 4 were added to a 2% NaOH alkaline solution to test the gas production at different times. See Table 1, which is a comparison of the gas production of the materials prepared in the examples of the present invention and the comparative examples.

[0069] Table 1

[0070] The faster the gas production time and the larger the gas production, the worse the uniformity and integrity of the carbon layer coating on the particle surface. It can be seen from the gas production results of the embodiments and comparative examples in Table 1 that the carbon layer coating on the surface of the silicon-carbon composite material prepared by the present invention has quantitative integrity and uniformity.

[0071] The above is a detailed introduction to the preparation method and application of a high-rate long-cycle silicon-carbon negative electrode material for lithium-ion batteries provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method and core ideas of the present invention, including the best mode, and also enables any technician in the field to practice the present invention, including the manufacture and use of any device or system, and the implementation of any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in several ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: The following steps are involved: In a protective atmosphere, carbon source gas is introduced, and plasma enhanced chemical vapor deposition is performed on silicon-carbon matrix raw material particles to obtain a silicon-carbon composite material with a carbon layer coated on the surface.

2. The preparation method according to claim 1, characterized in that: The plasma enhanced chemical vapor deposition is specifically low temperature plasma enhanced chemical vapor deposition; The gas temperature of the plasma enhanced chemical vapor deposition is 20-500°C.

3. The preparation method according to claim 1, characterized in that: The silicon-carbon matrix raw material particles include one or more of silicon-carbon particles doped with silicon and carbon, silicon-carbon particles with silicon compounded inside and / or on the surface of porous carbon particles, silicon-carbon particles with carbon compounded inside and / or on the surface of porous silicon particles, and silicon oxide / carbon particles; The particle size of the silicon-carbon matrix raw material particles is 0.1-15 μm.

4. The preparation method according to claim 1, characterized in that: The mass content of silicon in the silicon-carbon matrix raw material particles is 0.1% to 60%; The silicon-carbon matrix raw material particles include heated silicon-carbon matrix raw material particles.

5. The preparation method according to claim 4, characterized in that: The heating temperature is 1-500°C; The heating rate is 1-20°C / min.

6. The preparation method according to claim 1, characterized in that: The introducing of the carbon source gas specifically includes introducing the carbon source gas under the condition of using the protective gas as the carrier gas; The carbon source gas includes one or more of methane, acetylene, ethylene, propylene and propane; The protective gas includes one or more of an inert gas, nitrogen, and an inert gas / hydrogen mixed gas.

7. The preparation method according to claim 6, characterized in that: The flow rate of the protective gas is 0.1~100L / min; The flow rate of the carbon source gas is 0.1-20 L / min.

8. The preparation method according to claim 1, characterized in that: The power of the plasma enhanced chemical vapor deposition is 0.1~1KW; The plasma enhanced chemical vapor deposition time is 5 to 200 minutes.

9. The preparation method according to claim 1, characterized in that: The silicon-carbon composite material includes a silicon-carbon negative electrode material; The silicon-carbon composite material is specifically a silicon-carbon negative electrode material for lithium-ion batteries.

10. Use of the silicon-carbon composite material prepared by the preparation method according to any one of claims 1 to 9 in negative electrode materials for secondary batteries.

Citation Information

Patent Citations

  • Carbon-carbon nanotube-silicon nanoparticle and preparation method and application thereof

    CN110880592A

  • Silicon-carbon compound negative electrode material for secondary battery and preparation method of silicon-carbon compound negative electrode material

    CN113410445A

  • Silicon-carbon composite negative electrode material for secondary battery and preparation method of silicon-carbon composite negative electrode material

    CN113422017A

  • Low-expansion long-life silicon-carbon composite material and preparation method thereof

    CN115911326A

  • Silicon-carbon negative electrode material, preparation method thereof and secondary battery

    CN117821948A

Cited By

  • Silicon-carbon powder and manufacturing equipment thereof, and dispersion and adsorption process based on silicon-carbon powder

    CN119898758A

  • Battery slurry suitable for high-specific-surface-area three-dimensional composite silicon negative electrode material, battery pole piece and preparation method of battery pole piece

    CN121172110A

  • Battery slurry, battery pole piece and preparation method suitable for high specific surface area three-dimensional composite silicon negative electrode material

    CN121172110B